2015
DOI: 10.1097/ede.0000000000000313
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Urine Arsenic with Prevalent and Incident Chronic Kidney Disease

Abstract: Background Few studies have evaluated associations between low to moderate arsenic levels and chronic kidney disease (CKD). The objective was to evaluate the associations of inorganic arsenic exposure with prevalent and incident CKD in American Indian adults. Methods We evaluated the associations of inorganic arsenic exposure with CKD in American Indians who participated in the Strong Heart Study (SHS) in 3,851 adults aged 45–74 years in a cross-sectional analysis, and 3,119 adults with follow-up data in a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 84 publications
(64 citation statements)
references
References 55 publications
2
62
0
Order By: Relevance
“…Our contention that InAs excretion is impaired among those with reduced renal function is also supported by recent cross-sectional and prospective analyses of a large American Indian cohort with substantially lower As exposure than our study population (median total uAs 9.7 μg/L vs. 125 μg/L in our study) (Zheng et al, 2015). In the cross-sectional analysis of that cohort, urinary InAs concentrations were inversely associated with CKD prevalence (i.e.…”
Section: Discussionsupporting
confidence: 87%
“…Our contention that InAs excretion is impaired among those with reduced renal function is also supported by recent cross-sectional and prospective analyses of a large American Indian cohort with substantially lower As exposure than our study population (median total uAs 9.7 μg/L vs. 125 μg/L in our study) (Zheng et al, 2015). In the cross-sectional analysis of that cohort, urinary InAs concentrations were inversely associated with CKD prevalence (i.e.…”
Section: Discussionsupporting
confidence: 87%
“…Both of these studies accounted for urine concentration by correction with urine creatinine (i.e., exposure categorized as μg/g creatinine). However, a recent study in the Strong Heart cohort reported that the sum of inorganic and methylated arsenic species was inversely related to prevalent CKD and thus, similar to the positive associations we observed (Zheng et al, in press). Interestingly, arsenic was associated with increased risk for incident CKD.…”
Section: Discussionsupporting
confidence: 88%
“…Experimental and epidemiological studies support the role of chronic iAs exposure in arsenic toxicity (Hughes 2002). In particular, iAs exposure has been associated with cancer [International Agency for Research on Cancer (IARC) 2004], cardiometabolic disease (Moon et al 2012; Navas-Acien et al 2008), and kidney disease (Peters et al 2014; Zheng et al 2015). After entering the body, iAs undergoes two sets of reduction and methylation reactions to a trivalent state and oxidation to a pentavalent state, producing monomethylarsonate (MMA) and then dimethylarsinate (DMA) (Hughes 2002).…”
Section: Introductionmentioning
confidence: 99%